2020 Clinical practice guidelines for Myocarditis in adults - G. P. Arutyunov; F. N. Paleev; O. M. Moiseeva; D. O. Dragunov; A. V. Sokolova; A. G. Arutyunov; I. V. Zhirov; O. V. Blagova; E. V. Privalova; S. A. Gabrusenko; A. A. Garganeeva; G. E. Gendlin; et al. (Российский кардиологический журнал)
Russian Society of Cardiology (RSC)With the participation: Eurasian Association of Therapists (EUAT), Society of Specialists in Heart Failure (OSSN), Russian Scientific Medical Society of Therapists (RNMOT), Russian Society of Pathologists, Russian Society of Radiologists and Radiologists (RSR)Endorsed by: Research and Practical Council of the Ministry of Health of the Russian Federation